Ecological Preaching Communication Strategy as a Response to Social Change in the Digital Era: A Comparative Study of Al-Ittifaq Ciwidey Islamic Boarding School and Fish Bank Indonesia - Irfan Haniful Qoyyim; Muhammad Fahmi Syihab; Cecep Sunarya (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The global ecological crisis and contemporary social problems compel Islamic institutions to respond through concrete action rather than verbal preaching alone. This study analyzes ecological da'wah communication strategies in responding to social change through a comparative study of Pesantren Al-Ittifaq Ciwidey and Fish Bank Indonesia. Both institutions demonstrate how Islamic theological values are operationalized through action-based programs in distinct institutional contexts. This research employs a qualitative approach using comparative virtual ethnography and netnography on digital platforms, including Instagram accounts and official websites of both institutions. The study applies Contextual Da'wah Theory, Murray Bookchin's Social Ecology Theory, and the Transformative Da'wah framework. Findings reveal three convergent communication strategies: participatory engagement, educational empowerment, and digital amplification. Pesantren Al-Ittifaq integrates organic farming, waste recycling, and a cooperative network empowering 270 alumni farmers, generating a 300% increase in farmers' income since 1993. Fish Bank Indonesia implements circular economy principles through community-based waste management and environmental campaigns. Both institutions demonstrate that ecological da'wah bil hal, combined with strategic digital communication, functions as an effective agent of social transformation. This comparative analysis contributes a theoretical framework for understanding action-based ecological da'wah across different institutional types in Indonesia and recommends the tathwir-tamkin paradigm as a practical guide for designing sustainable ecological da'wah programs.